PENGARUH PENGGUNAAN VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA KELAS XII - Silvi Puspa Widya Lubis (Jurnal Dedikasi Pendidikan, 2017)
This study aims to determine the effect of the use of learning videos on the learning outcomes of class XII students. This research conducted at SMAN 1 RSBI Lubuk Pakam on March 2012. The population of the study was the students of class XII consisted of 179 students. In selecting the sample, researcher chose randomly sampling from 6 classes, and chose 2 classes to be as the sample. The first class was the experimental group and the second class was control group.  This research is a quasi experiment with One-shoot Study Case design. Data were analyzed by t test, using SPSS. The result showed that the students’ outcomes who learned by video was more effective than the students who did not learn by video. Based on the data analysis through SPPS with the significance 95% (p < 0,05), it found that t score was 0,037. The result showed that t score=(-2,127) < t table =(-2,043).